Dinâmica das relações afetivas: crenças e implicações para a vulnerabilidade à AIDS - Silva, Elis Amanda Atanázio da (2012)
Introduction: from the mid-18th century it was possible to see significant changes in ideas about romantic love, which began to gain importance, contributing to the secular and changes affecting the social life as a whole. The lives of men and women was reorganized and the beliefs and roles assumed by everyone in modern society were restored, revealing the emergence of other interpretative axes to sexuality and, consequently, the establishment of relationships. In this sense, the present study aimed to investigate the dynamics of emotional relationships of young adults in common-law, compared to their beliefs, satisfactions and compromises to fidelity, and the possible implications for vulnerability to HIVAIDS. For the Methodology, the sample consisted of 400 young adults of both sexes, with the age group 20 to 29 years old, heterosexual and who are in stable relationships. To the data collection instruments were used: 1) Romantic Beliefs scale; 2) scale of loving satisfaction; 3) related behaviors survey Infidelity; 4) Questionnaire of behaviors associated with vulnerability to HIVAIDS; 5) socio-demographic Questionnaire and additional information about the affective relationship. Questionnaire replies were given in Likert type scale with 10 points and the database has been built from the Statistical Software SPSS for Windows-versão18, with descriptive and bivariate analyses. The Results pointed to sample women as having romantic beliefs, which may be the most influential factor and exposure to vulnerability to HIV, because the majority is on the fickleness of the use of condoms in their sexual relations. Confidence in the partner was a reason stated by most participants as much to the absence in the use of condoms, as well as to the low membership in personal perception of vulnerability to AIDS. However, the behavior of infidelity linked to vulnerability to HIV has shown how unbreakable confidence in partner is mistaken, since the male participants, in greater numbers than women, they claimed they have already betrayed its partners, even if these unofficial relations have not always made use of the condom. The sample was characterized as satisfied lovingly, having men presented as more satisfied than women, or safer this satisfaction, or even lower. Therefore, it was noticeable that many of the recent practices carried out by young adults in common-law are re-signified by organizers of the sense that relate to traditional myths of romantic love, in which trust in partner claims its right to eternity, although the scope for freedom of the contemporary world, which corroborate in unprotected sexual practices. All of these components point to weaknesses in health promotion initiatives and HIVAIDS prevention, resulting in a situation of vulnerability.